The flavonoid GL‐V9 alleviates liver fibrosis by triggering senescence by regulating the transcription factor GATA4 in activated hepatic stellate cells. (20th December 2022) - Zhao, Jiawei; Bai, Dongsheng; Qi, Lei; Cao, Wangjia; Du, Jiaying; Gu, Chunyang; Zhou, Chen; Gao, Yuan; Zhang, Lulu; Zhao, Yue; Lu, Na
Abstract : Background and purpose: Liver fibrosis is a critical risk factor for the progression from chronic liver injury to hepatocellular carcinoma. Clinically, there is a lack of therapeutic drugs for liver fibrosis. Previous studies have confirmed that GL‐V9, a newly synthesized flavonoid derivative, exhibits anti‐inflammatory activity, but whether it has anti‐hepatic fibrosis actions remains unclear. This study aimed to investigate the anti‐fibrotic activities and potential mechanisms of GL‐V9. Experimental approach: Bile duct ligation (BDL) and carbon tetrachloride (CCl4 ) challenges were used to assess the anti‐fibrotic effects of GL‐V9 in vivo. Mouse primary hepatic stellate cells (pHSCs) and the human HSC line LX2 also served as a liver fibrosis model in vitro. Cellular functions and molecular mechanism were analysed using senescence‐associated beta‐galactosidase staining, real‐time PCR, western blotting, immunofluorescence, and co‐immunoprecipitation. Key results: GL‐V9 attenuated hepatic histopathological injury and collagen accumulation, as well as decreasing the expression of fibrotic genes in vivo. GL‐V9 promoted senescence and inhibited the expression of fibrogenic genes in HSCs in vitro. Mechanistic studies revealed that GL‐V9 induced senescence by upregulating GATA4 expression in HSCs. Further studies confirmed that GL‐V9 stabilized GATA4 by promoting autophagic degradation of P62. Conclusion and implications: GL‐V9 exerted potent anti‐fibrotic effects both in vivo and in vitro by stabilizing GATA4, thereby promoting the senescence of HSCs, and by avoiding its activation and ultimately inhibiting liver fibrosis. This action indicated that the flavonoid GL‐V9 is a potential therapeutic candidate for the treatment of liver fibrosis.